Mais tempo para quê?: A organização do currículo em uma escola em tempo integral da rede municipal de educação de São João - PR - Souza, Fernanda Ribeiro de (2016)
The full-time education has been the focus of intense debats and government strategies for its implementation in the Brazilian public school. In view of the More Education Program, created in 2007 as a strategy for inducing the expansion of the school time, we analyze the curricular settings in a public school, linked to the program, belonging to the municipality's education of São João, PR. The research aimed to analyze and to understand the curriculum designs that materialize, the organization of time, space and curriculum in the extended school day, as well as identify obstacles and advances for building an full-time school in a democratic and emancipatory perspective. The research of qualitative nature was performed by a case study. It was developed through analysis of official documents that guides the proposal of the More Education Program as well as the São João public education (Project of Integral Education and Pedagogic Curriculum Proposal for Integral Education and for the nine years elementary school) and the Municipal Countryside School Imaculada Conceição - EIEF (Politicalpedagogical Project and Plan of Action), scenery of this study. Questionnaires were administered to the managers of schools that offer the early years of elementary school to contextualize the full-time education and conducted semi-structured interviews with teachers and administrators who work in the researched school and in the Municipal Department of Education. The results show that the school time expansion reproduces the same elements of the partial shift, especially in view of the social demands and socialization, with little progress towards propitiating a new meaning to an emancipatory and implicated curricular project in full development of children and adolescents. We have not identified the question of curriculum and knowledge already laid and in the same way the effort to think new ways to socialize knowledge, in a transforming perspective. We found some key trends in training and curricular practices of the studied school: focus on the complement of the formal curriculum, the curriculum focused on the development of behaviors that promote learning of the common curriculum and, with less emphasis, the curriculum that targeted the learning of several languages and areas (dance, music, sport, recreation). Some weaknesses were found in the turn/reverse turn parallelism, in the difficulty of promoting curricular integration, in the juxtaposition of activities, in the absence of discussion and consensus on the conception about the Integral education longed, as well as on the school's social function in the Integral education perspective. The full-time school has sought to expand the formative opportunities and to improve the quality of public education, however, there are many challenges to overcome, among them emerges the necessity of continuing education, investments in infrastructure, improvements in the working conditions of the teachers, aiming that they have theoretical and material support to reorganize the curriculum and reframe their practices.